Peran dan Dampak Perumbuhan Ekonomi Terhadap Distribusi Pendapatan - Raysharie, Puput Iswandyah; Ananta, Asty; T, Donella Cleodora; Helena, Helena; Simandalahi, Lusiana Iswandyah; Putri, Mareta Novia; Yetno, Yetno (STIE Jambatan Bulan, 2025)
This study focuses on the aim of examining the influence of economic growth in Indonesia in 2023. In the era of globalization and economic dynamics, it is important for the government to control the increasingly crowded economy. Income is an important indicator in assessing the welfare of society and the economic stability of a country. Economic growth is considered a major factor in increasing income and reducing poverty. In this study presented the latest literature that covers a variety of theories and approaches in studying the correlation of economic growth free variables with income distribution bound variables. The results of this study of economic growth in 2023 have a positive and insignificant impact. This discovery could be the foundation for the economic growth plan that the government will undertake for more advanced Indonesia